Perilaku Masyarakat dalam Pemeliharaan Hutan Lindung di Banjar Kedisan, Desa Yehembang Kauh, Kecamatan Mendoyo, Kabupaten Jembrana - I DEWA NGAKAN INDRA PRASADA; NI WAYAN SRI ASTITI; M.TH. HANDAYANI. (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Society Behavior On conservation of Protected Forest in the Sub-Village of Kedisan, Yehembang Kauh Village, Mendoyo District, Jembrana Regency. The protected forest will be preserved by the society if the knowledge, attitude and action on the protected forest belong in the category of good and even very good. The aim of this study is to find out the behavior (knowledge, attitude, and action) of the society on conservation of protected forest in Sub-Village of Kedisan, Yehembang Kauh Village, Mendoyo District, Jembrana Regency. This research uses descriptive qualitative method of analysis. Based on the result of the study, it is revealed that people's behavior towards protected forest belongs in the category of ‘good’ in which reach the level of 80,50 %. In the level of knowledge falls into the category of